The Influence of Instagram Social Media Marketing on Brand Awareness: A Study of Jupiter Roastery, a Local Coffee MSME - Marfend, Reza; Yusup, Ismail; Rachmani , Nizza Nadya (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The rapid expansion of social media has empowered micro, small, and medium enterprises (MSMEs) to enhance brand communication through interactive and visual platforms. Jupiter Roastery, a local coffee MSME, actively leverages Instagram to promote its products and establish its brand identity. However, there remains a need to improve public recognition of the brand specifically as a roastery and supplier of roasted coffee beans. Employing a quantitative descriptive approach, this research examines the impact of Instagram Social Media Marketing on Brand Awareness at Jupiter Roastery. A purposive sample of 96 respondents completed a five point Likert scale questionnaire, and the collected data were analyzed via simple linear regression. The analysis demonstrates a positive and significant effect of Instagram marketing on Brand Awareness. Furthermore, the findings highlight that a major portion of the changes in Brand Awareness are attributable to these social media activities. Ultimately, the study concludes that engaging, consistent, and shareable Instagram content is crucial for elevating brand recognition and recall within the local coffee market.